The economics of the Common Market - Swann, Dennis (Harmondsworth : Penguin, 1972)
The book describes the social and political origins of the Six, traces its evolution through the practical decisions that have been taken since 1958, and indicates the possibilities of futures.
Bibliography: p. [209]-216.
osc 16/10/2018
Loans
Keywords: Economic integrtion